Key Factors Affecting AI Adoption Rate in Retail Business (Multiple Theory Perspectives) - Mulyanto, Dody (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
This study aims to identify and analyze the key factors that influence the adoption intention of Artificial Intelligence (AI) in retail businesses in Surakarta City. With the rapid development of technology, AI adoption has become an urgency for retail businesses to improve operational efficiency and customer experience. The research method used was quantitative with a survey approach, involving 135 randomly selected retail businesses. Data were collected through a questionnaire with a 5-point Likert scale and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed thatperceived ease of use,environmental factors andeffort expectancy had a positive and significant influence on AI adoption intention, while perceivedusefulness andperformanceexpectancy showed no significant influence. The limitations of this study lie in the limited geographical scope and small sample size. Future research is expected to expand geographic coverage and use a larger sample to increase the generalizability of the findings. In addition, future research can explore other factors that may influence AI adoption in different contexts.